2004
DOI: 10.1111/j.1464-410x.2003.04683.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal polyuria in community‐dwelling women

Abstract: OBJECTIVETo determine the age prevalence of nocturnal polyuria among older women in the community, and to investigate the relationship between nocturnal polyuria and nocturia. PATIENTS AND METHODSIn all, 1183 women aged ≥50 years, who were registered with a family doctor practice and who had taken part in a prevalence study, were sent brief questionnaires and a frequency/volume chart (FVC) to complete. RESULTSThere were 227 FVCs with adequate data and 264 completed questionnaires available for analysis. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
3
16
0
1
Order By: Relevance
“…41 This finding corresponds with studies by Swithinbank et al (women), 30 Rembratt et al (men and women), 31 and Massolt et al (incontinent women) 32 who found a markedly higher frequency of nocturnal polyuria in subjects having nocturia (≥ 2 voids) compared to no nocturia.…”
Section: Frequency Volume Chartssupporting
confidence: 87%
“…41 This finding corresponds with studies by Swithinbank et al (women), 30 Rembratt et al (men and women), 31 and Massolt et al (incontinent women) 32 who found a markedly higher frequency of nocturnal polyuria in subjects having nocturia (≥ 2 voids) compared to no nocturia.…”
Section: Frequency Volume Chartssupporting
confidence: 87%
“…Since publication of the ICS standardization report, several groups have used the ICS definition with 33% cutoff to present the percent of patients with or without NP. 1,4,8,10,[12][13][14][15][16] Others reported actual NPI values as the mean or sometimes as the median while a minority provided an indication of the variation by presenting the range, 17,18 SD 11,19 or percentile. 20 Of 14 studies including a total of 2,266 subjects, in which there is some overlap due to repeat use of data, we calculated a weighted mean NPI of 33%.…”
Section: Discussionmentioning
confidence: 98%
“…16,36 In contrast, Swithinbank et al reported that daytime urinary frequency has no relationship with nocturia or nocturnal polyuria in women. 93 No studies have reported an association between nocturia and voiding symptoms.…”
Section: Luts Other Than Nocturiamentioning
confidence: 99%